ESTETIKA ANALISA KARYA SENI DESAIN POSTMODEREN DENGAN PEMBAHASAN KONSEP IMAJINASI JEAN PAUL SARTRE - Widyastaguna, Putu Ryan (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2024)
Abstract Imagination is a process of the brain that captures the reaction of what we see, hear, and feel.The brain stores so much memory every day. Until the memory finally begins to form a pattern that then stimulates the brain to plan something and also someone's emotions can become an imagination.But One opinion of imagination was put forward by Jean paul Sartre, Sartre made a strong claim that the image given in the act of imagination can never be a source of knowledge, Sartre asserted that the attitude of imagination is indeed one observation, the fire is an observation that is not teaching nothing but an affirmation of emptiness. The author wants to analyze the work of postmoderen design by Fabio novembre with the discussion of the concept of the imagination of Sartre, This is the background of the author in the making of this paper, entitled: Analysis of artwork design postmoderen with the concept of imagination jean paul Sartre as for the conclusion obtained that is, In Novembre design work if viewed from the standpoint of sartre at the level of the design drawings of the novembre created is just a color on paper, then tend to consider the feelings that the audience has when looking at novembre design is an analogon and can take new quality based on the intention of the designers themselves against it.